Enhanced lithium storage property of Na-doped Li2Na2Ti6O14 anode materials for secondary lithium-ion batteries. Issue 52 (10th June 2015) - Lao, Mengmeng; Li, Peng; Lin, Xiaoting; Shao, Lianyi; Shui, Miao; Long, Nengbing; Wang, Dongjie; Shu, Jie
<x xml:space="preserve">Abstract</x> In this paper, a series of Na-doped Li2Na2Ti6O14 samples are synthesized by a simple solid-state reaction method through Li-site substitution with Na.